Human Mesenchymal Stromal Cells Resolve Lipid Load in High Fat Diet-Induced Non-Alcoholic Steatohepatitis in Mice by Mitochondria Donation - Sandra Nickel; Madlen Christ; Sandra Schmidt; Joanna Kosacka; Hagen Kühne; Martin Roderfeld; Thomas Longerich; Lysann Tietze; Ina Bosse; Mei-Ju Hsu; Peggy Stock; Elke Roeb; et al. (Cells, 2022)
Mesenchymal stromal cells (MSC) increasingly emerge as an option to ameliorate non-alcoholic steatohepatitis (NASH), a serious disease, which untreated may progress to liver cirrhosis and cancer. Before clinical translation, the mode of action of MSC needs to be established. Here, we established NASH in an immune-deficient mouse model by feeding a high fat diet. Human bone-marrow-derived MSC were delivered to the liver via intrasplenic transplantation. As verified by biochemical and image analyses, human mesenchymal stromal cells improved high-fat-diet-induced NASH in the mouse liver by decreasing hepatic lipid content and inflammation, as well as by restoring tissue homeostasis. MSC-mediated changes in gene expression indicated the switch from lipid storage to lipid utilization. It was obvious that host mouse hepatocytes harbored human mitochondria. Thus, it is feasible that resolution of NASH in mouse livers involved the donation of human mitochondria to the mouse hepatocytes. Therefore, human MSC might provide oxidative capacity for lipid breakdown followed by restoration of metabolic and tissue homeostasis.